Dendam Laksamana (PC game) / Muhammad Asyraf Yahaya...[et al.] - Yahaya, Muhammad Asyraf; Shawalludin, Syahrini; Moahamed, Salim (Universiti Teknologi MARA, Kedah, 2018)
Dendam Laksamana is a PC game with gameplay interaction with visual and narrative storylinetts emphasize on Malaysia culture where the character attire are according to Malay costume and combination with modern style.The videogame genre is a side-scrolling action game,and the on screen characters can generally only move to the left or right.ft follows the story of a guy named,Tantari.He is the greatest and well-known admiral.Suddenly,his homeland have been attacked by the evil gang,known as '6 Jahanam'Zhis happened because one of Tantari's comrade was a traltorftlow,Tantari seek for vengeance and will free his homeland.He will come from the shadowand slay the evilThe game is only for edutainment purposes,which is media designed to educate through entertainment.Most often it Includes content Intended to teach but has Incidental entertainment value.